PENGARUH PEMAHAMAN AKUNTANSI, DUKUNGAN KELUARGA DAN PERTIMBANGAN PASAR KERJA TERHADAP MINAT MAHASISWA AKUNTANSI MENJADI AKUNTAN PUBLIK - Renya Anjelina; Nugraeni (JURNAL ILMIAH EDUNOMIKA, 2026)
Public accounting profession plays an important role in maintaining the transparency, credibility, and accountability of financial statements used as a basis for decision-making. However, the number of public accountants in Indonesia is still relatively low compared to the number of accounting graduates each year. This study aims to determine the effect of accounting understanding, family support, and labor market considerations on the interest of accounting students at a Private University in Yogyakarta in choosing a career as a public accountant by using multiple linear regression analysis methods. The population in this study consisted of undergraduate accounting students at a Private University in Yogyakarta. Since the population was quite large, the researcher did not examine the entire population but selected a number of students considered representative of the population as the research sample. The sample was determined based on specific criteria. The results of the study indicate that family support does not affect students’ interest in pursuing a career as a public accountant. On the other hand, accounting understanding and labor market considerations have an effect on students’ interest in pursuing a career as a public accountant. keywords: accounting understanding, family support, labor market considerations, career interest, public accountant